Pengujian Beberapa Konsentrasi Bacillus thuringiensis Berliner dalam Mengendalikan Hama Ulat Daun Selada (Lactuca sativa) - Laoh, Jeltje Hennle; Fauzana, Hafiz (PEST Tropical Journal, 2003)
Field study of using Bacillus tiiuringiensisto control lettuce leaf worms conducted atfarmers Gardening area in Simpang Baru Panam Pekanbaru. The objectives of thisstudy was to evaluate the response of the lettuce leaf worms to the different level ofB. thuringiensis concentration. Arranged in Randomized Block Design with fourtreatments (concentration of B. thuringiensis 0.0 %, 0.1 %, 0.2 %, and 0.3 %) and fourreplications. The results indicated that there are significant differences In responsto the level of B. thuringiensis concentration (0.0 %, 0.1 %, 0.2 %, and 0.3 %.). Thisindicated also, that B. thuringiensis could be used to control lettuce leaf worms.The effective concentration to control lettuce leaf worms are 0.2 % and 0.3 %.